BI 1291583: a novel selective inhibitor of cathepsin C with superior in vivo profile for the treatment of bronchiectasis - Kreideweiss, Stefan; Schänzle, Gerhard; Schnapp, Gisela; Vintonyak, Viktor; Grundl, Marc A. (Inflammation research, 2023)
Background Airway inflammation in chronic inflammatory lung diseases (e.g. bronchiectasis) is partly mediated by neutrophil-derived serine protease (NSP)/antiprotease imbalance. NSPs are activated during neutrophil myelopoiesis in bone marrow by cathepsin C (CatC; DPP1). CatC is therefore an attractive target to reduce NSP activity in the lungs of patients with bronchiectasis, restoring the protease/antiprotease balance. We report results from the preclinical pharmacological assessment of the novel CatC inhibitor BI 1291583. Methods Binding kinetics of BI 1291583 to human CatC were determined by surface plasmon resonance. In vitro inhibition of human CatC activity was determined by CatC-specific fluorescent assay, and selectivity was assessed against related cathepsins and unrelated proteases. Inhibition of NSP neutrophil elastase (NE) production was assessed in a human neutrophil progenitor cell line. In vivo inhibition of NE and NSP proteinase 3 (PR3) in bronchoalveolar lavage fluid (BALF) neutrophils after lipopolysaccharide (LPS) challenge and distribution of BI 1291583 was determined in a mouse model. Results BI 1291583 bound human CatC in a covalent, reversible manner, selectively and fully inhibiting CatC enzymatic activity. This inhibition translated to concentration-dependent inhibition of NE activation in U937 cells and dose-dependent, almost-complete inhibition of NE and PR3 activity in BALF neutrophils in an in vivo LPS-challenge model in mice. BI 1291583 exhibited up to 100 times the exposure in the target tissue bone marrow compared with plasma. Conclusion BI 1291583-mediated inhibition of CatC is expected to restore the protease–antiprotease balance in the lungs of patients with chronic airway inflammatory diseases such as bronchiectasis.